A large and feasible national survey representative of population exposure to outdoor gamma radiation in urban areas - Carpentieri, Carmela; Maiorana, Andrea; Ampollini, Marco; Antignani, Sara; Caprio, Mario; Carelli, Vinicio; Cordedda, Carlo; Di Carlo, Christian; Bochicchio, Francesco (Frontiers in Public Health, 2024)
Background: Although data on outdoor gamma radiation are available for many countries, they have generally been obtained with measurements performed in undisturbed environments instead of in urban areas where most of the population lives. Only one large national survey, with on-site measurements in urban areas, has been found worldwide, probably due to high costs (e.g., personnel, instrumentation) and difficulties in selecting measuring points.Methods: A campaign of outdoor gamma radiation measurements has been carried out in the entire Italian territory. All the measurement points were chosen at the infrastructures of an Italian telecommunications company as representative of all the possible situations of population outdoor exposure to gamma radiation in urban areas. Ten replicates of portable X-gamma detectors carried out all the measurements.Results: About 4000 measurements have been performed. They are distributed in 2901 Italian municipalities, accounting for 75% of Italian population. The national population-weighted mean of gamma ambient dose equivalent rate (ADER) is 117 nSv h -1 , and it ranges for 21 regions and 107 provinces from 62 to 208 nSv h -1 and 40 to 227 nSv h -1 , respectively. The average variability at the municipal level, in terms of coefficient of variation (CV) is 21%, ranging from 3% to 84%. The impact of the land coverage and the distance from a building on the outdoor gamma radiation level was assessed with complementary measurements, leading to differences ranging from -40% to 50% and up to 50%, respectively.A representative campaign of outdoor gamma dose rate measurements has been performed in Italy, only in urban areas, to assess population exposure due to outdoor gamma radiation. This is the largest national campaign in urban areas worldwide, with a total of 3876 on-site measurements. The land coverage and the distance from surrounding buildings were recognized to strongly affect outdoor gamma radiation levels, leading to high variability within small areas. The collaboration with a company that owns a network of facilities on a national territory as dense as the residing population made this survey feasible and affordable. Other countries might adopt this methodology to conduct national surveys in urban environments.